Theoretical insights on the reaction pathways for oxygen reduction reaction on phosphorus doped graphene. (August 2016) - Bai, Xiaowan; Zhao, Erjun; Li, Kai; Wang, Ying; Jiao, Menggai; He, Feng; Sun, Xiaoxu; Sun, He; Wu, Zhijian
Abstract: The reaction mechanisms for oxygen reduction reaction (ORR) on phosphorus doped divacancy graphene (P-GDV ) are investigated by using the density functional theory method. Our results showed that all of the possible ORR elementary reactions could take place within a small region around the P atom and its adjacent four carbon atoms. The hydrogenation of O2 molecule which forms OOH and hydrogenation of OOH which forms H2 O + O have negligible energy barrier. This reaction pathway is also the kinetically most favorable. The rate-determining step is the final step in the pathway, i.e., the hydrogenation of OH into H2 O with an energy barrier of 0.85 eV. Therefore, ORR mechanism on P-GDV would be a four electron process. The free energy diagram of the ORR predicted that for the most favorable pathway, the working potential is 0.27 V. Consequently, our theoretical study suggests that P doped graphene with intrinsic carbon defects could possess good catalytic activity for ORR.